Perbandingan Penanda Inflamasi dan Elastisitas Vaskular antara Mahasiswa Kedokteran Prehipertensi dan Normotensi di Jakarta - Wibowo, Naufal Rafi Kusuma; Bustamam, Nurfitri; Bahar, Meiskha; Purwaningastuti, Diana Agustini (Jurnal Kedokteran Meditek, 2025)
Introduction: An unhealthy lifestyle among medical students maycontribute to inflammation, reduced vascular elasticity, andincreased blood pressure. However, cardiovascular risk in theseyoung adults remains less explored compared to hypertensivepatients. Purpose: This study compares inflammatory markers andvascular elasticity in prehypertensive and normotensive medicalstudents. Methods: A case-control study utilizing simple randomsampling was conducted in the medical student population, included54 prehypertensive or normotensive subjects with no history ofhematological disorders, autoimmune diseases, cancer, diabetesmellitus, or cardiovascular medication use. Vascular elasticity,blood pressure, and inflammatory markers were assessed using anaccelerated photoplethysmograph, a digital sphygmomanometer,and a hematology analyzer. Results: A total of 25 subjects (46.3 %)had suboptimal vascular elasticity, 30 (55.6%) had a highneutrophil-to-lymphocyte ratio (NLR), and 40 (74.1%) exhibited alow-risk platelet-to-lymphocyte ratio (PLR). The Chi-square testrevealed a significant difference in NLR between prehypertensiveand normotensive students (p = 0.000; OR = 7.0; CI = 2.3–20.7),while no significant difference was observed in PLR (p = 0.525).Vascular elasticity also differed significantly between groups (p =0.000; OR = 5.2; CI = 2.0-13.2). Conclusion: Prehypertensivesubjects had higher NLR, and those with suboptimal vascularelasticity had higher prehypertension risk. These findings highlightthe need for cardiovascular risk assessment in young adults.